Pengaruh Devidend Payout Ratio, Devidend Yield, Ukuran Perusahaan, Volume Perdagangan, Nilai Tukar, Inflasi, dan Tingkat Suku Bunga Terhadap Volatilitas Harga Saham pada Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia Tahun 2012-2016 - Syarifah Nur Azura; Myrna Sofia; Nurhasanah Nurhasanah; Firmansyah Kusasi (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
The aims of this study is to look at the effect of Devidend Payout Ratio, Devidend Yield, Company Size, Trading Volume, Exchange Rate, Inflation, Interest Rate Against Stock Price Volatility. With a purposive sampling technique, this study took 7 companies as samples of 153 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. Data analysis was performed using Multiple Regression. The results of the study show that the Devidend Payout Ratio has an effect on Stock Price Volatility, while the Devidend Yield, Company Size, Trading Volume, Exchange Rate, Inflation and Interest Rate do not affect the Stock Price Volatility. While simultaneously all the independent variables tested showed a significant effect on Stock Price Volatility in Manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016.